Analysis of a Batch Adsorber Analogue for Rapid Screening of Adsorbents for Postcombustion CO 2 Capture - Balashankar, Vishal Subramanian (2019)
A simplified proxy model based on a well-mixed batch adsorber for vacuum swing adsorption (VSA) based CO2 capture from dry post-combustion flue gas is presented. A graphical representation of the model output allows for the rationalization of broad trends of process performance. The results of the simplified model are compared with a detailed VSA model that takes into account mass and heat transfer, column pressure drop and column switching, in order to understand its potential and limitations. A new classification metric to identify whether an adsorbent can produce CO2 purity and recovery that meet current US Department of Energy (US-DOE) for post-combustion CO2 capture and to calculate the corresponding parasitic energy is developed. The model, which can be evaluated within a few seconds, showed a classification Matthew correlation coefficient of 0.76 compared to 0.39, the best offered by any traditional metric. The model was also able to predict the energy consumption within 15% accuracy of the detailed model for 83% of the adsorbents studied. The developed metric and the correlation are then used to screen NIST/ARPA-E database to identify promising adsorbents for CO2 capture applications.